FDTD Investigation of Efficient and Robust Integration Between Si3N4and Ge-Rich GeSi for Waveguide-Integrated Electro-Absorption Optical Modulators - Khongpetch, Natdanai; Traiwattanapong, Worawat; Chiangga, Surasak; Limsuwan, Pichet; Chaisakul, Papichaya (My University, 2023)
Si3N4 photonic integrated circuits have gain significant and rapid interest in different photonic applications thanks to its superior passive performance. Nevertheless, optical integration between Si3N4 and Ge-based optical components remains critically challenging especially for optical modulation. In this paper, via 3D-FDTD calculations we investigate the optical integration between Si3N4 and Ge-based waveguides using vertical coupling configuration employing amorphous Si (α-Si) as an optical bridge showing efficient and robust coupling efficiency, which can be maintained according to the tolerant analysis with respect to the variations in optical wavelengths and critical parameters of the coupling structure. In addition, with respect to the recent theoretically-optimized SOI waveguide-integrated and also laterally-coupled Si3N4 waveguide-integrated Ge-based optical modulators, we found that the studied coupling structure could be employed to enable a low-voltage Si3N4 waveguide-integrated Ge-based optical modulator with a competitive extinction ratio/insertion loss performance, increasing the prospect of Si3N4-based photonic integrated circuits for low-energy optical interconnects.
Keywords: germanium; photonic integrated circuits; Si3N4; Waveguide